(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2016)
This study aims to determine the structure comunity and composition of insects in the swamp water of Deling Ogan Ilir on South Sumatera province, inÂ September to November 2012. Identification of aquatic insects in the Laboratory of Biology, Faculty of Mathematics and Natural Sciences University of PGRI Palembang. The results showed the relative density , relative frequency , relative dominance at station 1 ( Kumpai Padi ) and station 2 ( Lotus ) is Belostoma flumineum. Insects are the most dominant with the highest importance value index station 1 and station 2 Belostoma flumineum. While the insect species diversity index of water at station 1 of 1,54,Â at station 2 of 1,96 and index between stations by 17 %. Â Key words : Insects water , lebak swamp deling , structure , composition and communitas